Kedudukan Tenaga Kerja Wanita yang Terikat Pernikahan: Kajian Hukum Perdata dan Hukum Perdata Islam - Amaliah, Rezki; Wulan, Retno; Alimuddin, Hardiyanti (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This study aims to analyze the position of female workers who are bound by marriage in the perspective of civil law and Islamic civil law. The main issue raised is how these two legal systems regulate the rights and obligations of married female workers, as well as how legal protection is provided to them. The subject matter includes a comparison between the provisions in the civil law applicable in Indonesia and the principles contained in Islamic civil law regarding the status and rights of married women workers. The research method used is normative juridical with a comparative legal approach. This research examines various primary legal sources such as laws, government regulations, and ulama fatwas, as well as secondary sources such as books, scientific journals, and legal articles. The data collected were analyzed qualitatively to understand how the two legal systems govern the rights of married women workers. The results show that both civil law and Islamic civil law provide protection for the rights of married women workers, although there are differences in implementation and emphasis. Civil law emphasizes normative rights such as maternity leave, maternity leave, and protection against termination of employment due to marital status. Meanwhile, Islamic civil law emphasizes the principles of justice and the balance of rights and obligations between husband and wife, with an emphasis on the protection of women's rights in the scope of family and work. The novelty of this study lies in the comparative approach used to identify similarities and differences in legal protections for female workers bound by marriage under two different legal systems. The study also provides recommendations for policymakers to improve legal protections for married female workers, by integrating the positive aspects of both legal systems.